Efforts to Eliminate Social Classes as an Implementation of Multicultural Islamic Education: A Study of the Educational Empowerment Program at the Ar Ridho Foundation - Rahmawati, Indah; Truna, Dody S.; Rosyad, Rifki (UIN Sunan Gunung Djati Bandung, 2024)
The Ar Ridho Foundation is an institution that actively empowers orphans and the poor through educational programs that emphasize equality, inclusivity, and the elimination of social classes. In the context of multicultural Islamic education, efforts to eliminate social classes are an important aspect that is rarely studied in depth, especially at the level of religious institutional practice. This phenomenon is important to study because it shows how Islamic values ​​​​of human equality, respect for dignity, and empowerment can be realized through structured educational programs. This study aims to analyze the implementation of multicultural Islamic education at the Ar Ridho Foundation and identify educational empowerment strategies used to eliminate social classes between orphans and the poor and children in general. The research method uses a qualitative approach with a case study, involving in-depth interviews, moderate participant observation, and documentation as data collection techniques. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions interactively. The results show that the Ar Ridho Foundation implements multicultural Islamic education through a commensurate institutional culture, non-discriminatory social interaction, and educational programs such as tutoring, educational counseling, career guidance counseling, and the provision of technological facilities. These programs have been shown to improve academic ability, self-confidence, and educational opportunities, significantly reducing class barriers. This study recommends expanding educational collaboration, improving learning facilities, and strengthening mentors' capacity as strategic steps to enhance the sustainability of class-based education efforts.